On the stacking behavior of functionalized single-wall carbon nanotubes - Kukovecz, A.; Kramberger, Ch.; Holzinger, Michael; Kuzmany, Hans; Schalko, J.; Mannsberger, M.; Hirsch, Andreas (Journal of Physical Chemistry B, 2002)
Single-wall carbon nanotubes (SWNTs) were oxidatively functionalized by nitric acid treatment. The presence of carboxyl groups was proven by IR spectroscopy, matching earlier IR and NMR observations. Raman spectra in the radial breathing mode (RBM) and G line spectral windows were measured with six laser lines ranging from 457 to 647 nm. The RBM mode was observed to upshift by the functionalization with very little change in the spectral line shape. By the analysis of the spectral moments of the lines, this upshift is interpreted as a change in an empirical intertube interaction function. In agreement with previous TEM results, we have found that bundles in a pristine SWNT sample are significantly thinner (< 10 tubes) than those in the oxidized samples (> 30 tubes). Changes observed in solvatation properties and sample morphology could be explained on this basis. Our observations suggest that carboxyl related secondary bonding forces might also play a role in the stacking of oxidized SWNTs.